Prognostic value of the PDLIM family in acute myeloid leukemia - Cui, Longzhen (Am J Transl Res, 2019)
Acute myeloid leukemia (AML) is a genetically complex, highly aggressive hematological malignancy. Prognosis is usually with grim. PDZ and LIM domain proteins (PDLIM) are involved in the regulation of a variety of biological processes, including cytoskeletal organization, cell differentiation, organ development, neural signaling or tumorigenesis. The clinical and prognostic value of the PDLIM family in AML is unclear. To understand the role of PDLIM expression in AML, The Cancer Genome Atlas (TCGA) database was screened and 155 de novo AML patients with complete clinical information and the expression data of the PDLIM family were included in the study. The clinical and molecular characteristics associated with the expression of different members of the PDLIM family were summarized using various statistical methods. In 84 patients who only received chemotherapy, univariate analysis indicated that high expression of PDLIM2 or PDLIM7 was associated with shorter EFS and OS (both P<0.05 for PDLIM2, and both P<0.01 for PDLIM7). Multivariate analysis suggested that high expression of PDLIM7 was an independent risk factor for EFS and OS (both P<0.05). In the other 71 patients who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT), survival was unaffected by PDLIM expressions. In summary, high expression of PDLIM2 and PDLIM7, especially the latter, could serve as adverse prognostic factors for AML, but their prognostic effects could be reversed by allo-HSCT.